2011
DOI: 10.1016/j.jdent.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacterial deactivation using a low-temperature atmospheric argon plasma brush

Abstract: Summary Objectives To study the plasma treatment effects on deactivation effectiveness of oral bacteria. Methods A low temperature atmospheric argon plasma brush were used to study the oral bacterial deactivation effects in terms of plasma conditions, plasma exposure time, and bacterial supporting media. Oral bacteria of Streptococcus mutans and Lactobacillus acidophilus with an initial bacterial population density between 1.0 × 108 and 5.0 × 108 cfu/ml were seeded on various media and their survivability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 19 publications
(17 reference statements)
2
55
0
2
Order By: Relevance
“…Thus, bacterial size and structure may affect plasma effectiveness in bacterial deactivation. Yang et al [68] reported the bactericidal effect of TTP on S. mutans and L. acidophilus, which are major pathogens in dental caries. The results indicated that TTP treatment was very effective in the disinfection of oral bacteria.…”
Section: Tissue-tolerable Plasma In Dentistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, bacterial size and structure may affect plasma effectiveness in bacterial deactivation. Yang et al [68] reported the bactericidal effect of TTP on S. mutans and L. acidophilus, which are major pathogens in dental caries. The results indicated that TTP treatment was very effective in the disinfection of oral bacteria.…”
Section: Tissue-tolerable Plasma In Dentistrymentioning
confidence: 99%
“…They found that L. acidophilus killing needed a longer TTP exposure when compared with S. mutans. One of the hypotheses is that L. acidophilus presents a larger cell (≅1 μm×3 μm), which could mean higher plasma tolerance when compared with the smaller S. mutans(≅1 μm in diameter) [68]. To accomplish the same killing intensity, up to 5 min of TTP exposure was necessary to deactivate L. acidophilus, which is contrary to the 10 s of TTP exposure needed to kill S. mutans.…”
Section: Tissue-tolerable Plasma In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…CAP technologies have been used effectively to eliminate microorganisms on living tissues in several clinical applications [8,80,[94][95][96][97][98][99][100][101] , including inactivation and eradication of fungi, and vegetative and spore-forming bacteria. [86,89,102] The microbial inactivation effect of CAP can be attained by direct exposure to both the ignited plasma discharge products such as ROS, RNS, UV radiation, or indirectly through the long-lived species that are capable to reach the treated substrate without the electric field effect [91] .…”
Section: Mechanisms Of Microbial Inactivation By Capmentioning
confidence: 99%
“…Yang et al 11) investigated the bactericidal effect of a non-thermal atmospheric-pressure plasma brush on S. mutans and L. acidophilus, which are major pathogens in dental caries. Their results indicated that cold plasmas were effective in deactivating oral bacteria in culture after 5 min of application, this might play some roles in prevention or treatment of dental caries.…”
Section: Introductionmentioning
confidence: 99%